METHODOLOGY FOR ECOLOGICAL ECONOMIC SYSTEM EFFICIENCY EVALUATION - Tunytsya , Yuriy (Forestry, Forest, Paper and Woodworking Industry, 2009)
Ecological economics assumes the organic unity of the ecological economic system both at macroeconomic and microeconomic levels. It reveals the main tensions between economic re-quirements and ecological imperatives and finds the ways of overcoming these tensions both at the sector and territorial levels. Natural resources and ecosystem services should be considered within the framework of the unified ecological economic system. The human use of the environment should be understood as a threefold process of sustainable use, protection, and regeneration of the ecological eco-nomic system. The goals of preventing the loss of ecological potential and achieving sustainable de-velopment may be reached by two ways: the first is to bring the production technology into correspon-dence with ecological imperatives; the second is goal-oriented environmental protection activity. The ecological-economic effect is based on the net economic effect of the production-economic activity minus ecological costs and losses. The notion of «ecological economic cost-effectiveness» equally corresponds to the development laws of society and nature and therefore satisfies the principle of sustainable development. Forest presents a very good model for the eco-economic system. The problem of ecological economic cost-effectiveness in forestry is so complex that the approach used to solve it can illustrate the possible ways of ecological economic problems solving in general.